HUBUNGAN SOSIAL EKONOMI TERHADAP KEMISKINAN DI KECAMATAN ULIM DAN MEURAH DUA - Ferayanti -; Cut Risya Varlitya (Syiah Kuala University, 2017)
Poverty can cause the difficulties for population in meeting their basic needs. This study aims to examine the relationship between socio-economic variables to poverty in Ulim and Meurah Dua sub-districts which are the poorest sub-districts in Pidie Jaya District. The research method used is a qualitative approach analysis based on secondary and primary data. The result shows that the economic condition of the population in Ulim and Muara Dua sub-districts is closely related to economic condition in Pidie Jaya District.